2014
DOI: 10.1371/journal.pone.0108903
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Tobacco Use Modify the Impact of Genetic Variants on the Occurrence of Conotruncal Heart Defects

Abstract: Conotruncal heart defects (CTDs) are among the most severe birth defects worldwide. Studies of CTDs indicate both lifestyle behaviors and genetic variation contribute to the risk of CTDs. Based on a hybrid design using data from 616 case-parental and 1645 control-parental triads recruited for the National Birth Defects Prevention Study between 1997 and 2008, we investigated whether the occurrence of CTDs is associated with interactions between 921 maternal and/or fetal single nucleotide polymorphisms (SNPs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Data from epidemiology research suggest that folate, glutathione, and homocysteine metabolism related genetic variants in maternal and fetal may have great impact on the heart development [57]. It had been reported that obesity mothers who carried mutant genotype AC for glutamate-cysteine ligase, catalytic subunit ( GCLC ) gene (rs6458939) significantly increased the risk of conotruncal defects (CTDs) in infants, compared with those obesity mothers who carried the CC genotype [58]. Another possible mechanism is that maternal metabolic environment plays an important role in fetal developments [59].…”
Section: Discussionmentioning
confidence: 99%
“…Data from epidemiology research suggest that folate, glutathione, and homocysteine metabolism related genetic variants in maternal and fetal may have great impact on the heart development [57]. It had been reported that obesity mothers who carried mutant genotype AC for glutamate-cysteine ligase, catalytic subunit ( GCLC ) gene (rs6458939) significantly increased the risk of conotruncal defects (CTDs) in infants, compared with those obesity mothers who carried the CC genotype [58]. Another possible mechanism is that maternal metabolic environment plays an important role in fetal developments [59].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke and maternal obesity were recently evaluated as environmental exposures interacting with both maternal and fetal variants of 60 genes involved in metabolic pathways associated with CTDs (folate, homocysteine, and trans-sulfuration) [18]. No SNP was associated with risk of CTD in the absence of tobacco exposure, and no protective SNP was identified.…”
Section: Gene Environment Interactionmentioning
confidence: 99%
“…In isolation, these results offer an unclear image of the biological impact of harboring any given CNV and, therefore, limit genotype-phenotype associations and predictions. Tobacco smoke and maternal obesity were recently evaluated as environmental exposures interacting with both maternal and fetal variants of 60 genes involved in metabolic pathways associated with CTDs (folate, homocysteine, and trans-sulfuration) [18]. No SNP was associated with risk of CTD in the absence of tobacco exposure, and no protective SNP was identified.…”
Section: Copy Number Variationsmentioning
confidence: 99%